The Effect of Reducing Electric Car Purchase Incentives in the European Union - Jonatan J. Gómez Vilchez; Christian Thiel (World Electric Vehicle Journal, 2019)
The importance of electric car purchase incentives is starting to be questioned. The objective of this paper is to explore the potential effect of reducing or removing electric car purchase public subsidies in the European Union. To this end, the system dynamics Powertrain Technology Transition Market Agent Model is used. The size and timing of purchase incentives for this technology in European countries are investigated under eight scenarios and sensitivity analysis performed. The simulations suggest that, in the short-run, the electric car market share is higher when the subsidies remain in place. In the medium-run, a purchase subsidy scheme granting €3000 for plug-in hybrid electric cars and €4000 for battery electric cars over the period 2020−2024 yields the fastest electric car market uptake of all the scenarios considered. We conclude that, though the current evolution of the battery price is favorable, electric car purchase subsidies remain an effective policy measure to support electro-mobility in the next years.